Learning Instructional Planning: Evolution, Sources of Change, and Learning Processes - Le Vân, Kim; Berger, Jean-Louis (Swiss Journal of Educational Research, 2018)
Instructional planning is one of the core competencies teachers develop during their training. Sources and processes that shape the learning of instructional planning practices remain largely unexplored. Thirty semi-structured interviews conducted with recently graduated teachers show a panel of instructional planning practices, which are learned and valued by teachers. Moreover, these practices rely on variable sources not limited to teacher education, but also on formal, non-formal, and informal learning. Thus, this study reveals how factors influencing the evolution of instructional practices are articulated.